Eastern enlargement of the EU: Jobs, investment and welfare in present member countries - Ben J. Heijdra; Christian Keuschnigg; Wilhelm Kohler (Johannes Kepler University of Linz, Department of Economics, 2001)
Eastern enlargement of the EU promises gains, but also imposes fiscal costs on incumbent countries. A sensitive issue concerns immigration, jobs and wages. We address these issues in a general equilibrium framework, both analytically and through numerical simulations. Analytical results identify capital accumulation as a prime transmission channel. Using a dynamic CGE model with search unemployment of high- and low-skilled labor, we simulate the effects of enlargement on Germany finding small e.ects from trade, but more pronounced labor market e.ects from migration. Based on German model elasticities, we approximate expected benefits and costs for other member countries as well.
Keywords: C68; F13; F15; 330; enlargement; economic integration; economic growth; capital accumulation; search unemployment; computable general equilibrium analysis; EU-Erweiterung; Internationale Wanderung; Beschäftigungseffekt; Allgemeines Gleichgewicht; Wohlfahrtsanalyse; Deutschland; Osteuropa